Lemna minor plants chronically exposed to ionising radiation RNA-seq analysis indicates a dose rate dependent shift from acclimation to survival strategies - Van Hoeck, Arne (Plant science : an international journal of experimental plant biology, 2017)
Copyright © 2017 Elsevier B.V. All rights reserved.